Analisis Biaya Produksi Dan Laba Dalam Menentukan Harga Jual Air Minum Dalam Kemasan (AMDK) Pada Pabrik Air Mineral Madina (Study Kasus CV. Madina Murni) - Nisa, Khoirun; Hermain, Hendra; Hasibuan, Reni Ria Armayani (Journal of Student Development Informatics Management (JoSDIM), 2023)
This study aims to determine the calculation of production costs and profits to be the basis for determining the selling price of Bottled Mineral Water (AMDK) at the Madina mineral water factory. Based on the results of the analysis carried out by the researcher, several results were obtained that the calculation of production costs for determining the selling price at the Madina Mineral Water Factory used the full costing method, but the company did not include the cost of electricity for the water suction pump in the port of standard materials as a result, the total cost of production, the cost of production and the selling price found by the researcher using the cost plus pricing method is higher than that used by the company.